Locomotor behavior of Neocaridina palmata: a study with leachates from UV-weathered microplastics - Kristina Klein (PeerJ Inc., 2021)
Weathering of plastics leads to the formation of increasingly smaller particles with the release of chemical compounds. The latter occurs with currently unknown environmental impacts. Leachate-induced effects of weathered microplastics (MPs) are therefore of increasing concern. To investigate the toxicity of the chemical mixtures from such plastics, we exposed the freshwater shrimp Neocaridina palmata to enriched leachates from unweathered and artificially weathered (UV-A/B light) MPs (≤1 mm) from recycled low-density polyethylene (LDPE-R) pellets and from a biodegradable, not fully bio-based starch blend (SB) foil. We analyzed the individual locomotor activity (moved distance and frozen events) on day 1, 3, 7 and 14 of exposure to five leachate concentrations equivalent to 0.40–15.6 g MPs L−1, representing the upper scale of MPs that have been found in the environment. The median moved distance did not change as a function of concentration, except for the unweathered SB treatment on day 14 that indicated hyperactivity with increasing concentrations. Significant impacts were solely detected for few concentrations and exposure days. Generally, no consistent trend was observed across the experiments. We further assessed the baseline toxicity of the samples in the Microtox assay and detected high bioluminescence inhibitions of the bacterium Aliivibrio fischeri. This study demonstrates that neither the recycled nor the biodegradable material are without impacts on test parameters and therefore cannot be seen as safe alternative for conventional plastics regarding the toxicity. However, the observed in vitro toxicity did not result in substantial effects on the behavior of shrimps. Overall, we assume that the two endpoints examined in the atyid shrimp N. palmata were not sensitive to chemicals leaching from plastics or that effects on the in vivo level affect other toxic endpoints which were not considered in this study.